2021
DOI: 10.1016/j.jjcc.2020.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Secondary sarcopenia assessed by computed tomography can predict hospitalization for heart failure in adults with Fontan circulation

Abstract: Sarcopenia is a loss of muscle mass and function [1]. This phenomenon occurs not only in elderly people but also in patients with chronic illnesses such as, chronic heart failure (HF), liver dysfunction, and kidney dysfunction [1-5], which is called secondary sarcopenia. Possible explanations for sarcopenia include an abnormal energy metabolism coupled with mitochondrial dysfunction as well as a change in the structure of the myofibers, malnutrition, systemic inflammation, and oxidative stress [6][7][8][9].Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Alternative measures of somatic growth and body composition such as subcutaneous fat, triceps skinfold measurements, muscle mass, head circumference, bioelectrical impedance and whole‐body dual X‐ray absorptiometry were beyond the scope of this review, but have been investigated in the single ventricle population by others. 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 These studies have shown sarcopenia and deficits in bone density and structure to be major components of body composition in Fontan patients. Second, selection bias is plausible because most participants were by definition considered good candidates for the Fontan procedure; these data therefore assume that a thorough clinical assessment has preceded the decision to pursue the Fontan trajectory and may not be representative of the overall single ventricle population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative measures of somatic growth and body composition such as subcutaneous fat, triceps skinfold measurements, muscle mass, head circumference, bioelectrical impedance and whole‐body dual X‐ray absorptiometry were beyond the scope of this review, but have been investigated in the single ventricle population by others. 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 These studies have shown sarcopenia and deficits in bone density and structure to be major components of body composition in Fontan patients. Second, selection bias is plausible because most participants were by definition considered good candidates for the Fontan procedure; these data therefore assume that a thorough clinical assessment has preceded the decision to pursue the Fontan trajectory and may not be representative of the overall single ventricle population.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative measures of somatic growth and body composition such as subcutaneous fat, triceps skinfold measurements, muscle mass, head circumference, bioelectrical impedance and whole-body dual X-ray absorptiometry were beyond the scope of this review, but have been investigated in the single ventricle population by others. [59][60][61][62][63][64][65][66] These studies have shown sarcopenia and deficits in bone density and structure to be major components of body composition in Fontan patients.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In a retrospective study of 154 patients with Fontan circulation, a lower volume of the large lumbar muscle on an abdominal CT scan was associated with a higher risk of hospitalization for heart failure [ 12 ]. Oh et al found a lower likelihood of postoperative complications and prolonged intensive care bed stays after Fontan surgery in patients with a higher SMI (Th4) detected on preoperative CT scans [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41] Secondary sarcopenia has been implicated as both a cause and consequence of HF. Secondary sarcopenia is one of the important predictors of HF in non-chronic heart disease 42 and has a negative impact on the prognosis of HF in this population. Whereas it remains unclear how biological mechanisms aggravate sarcopenia in older adults with HF.…”
Section: Discussionmentioning
confidence: 99%